Pendampingan Wawasan Keagamaan dalam Meningkatkan Sikap Spiritual Anak di Desa Kepuhrubuh Kabupaten Ponorogo: Religious Insight Assistance in Improving Children's Spiritual Attitudes in Kepuhrubuh Village, Ponorogo Regency - Wiwin Rif’atul Fauziyati (Edujavare Publishing, 2023)
Kepuhrubuh Village, located in Ponorogo Regency, faces challenges in developing religious insight and strengthening children's spiritual attitudes. So, a mentoring effort is needed to increase understanding and religious values in order to shape children's spiritually strong character. This service aims to provide religious insight assistance to children in Kepuhrubuh Village with a focus on improving spiritual attitudes. Through this activity, it is hoped that they can increase their understanding of religious values and help shape positive spiritual character. This service method applies the participatory Action Research (PAR) method by involving the local community, especially parents, ustadz/ustadzah, and religious leaders. Accompanying activities include training, group discussions and other interactive activities to strengthen children's religious understanding. The results of this service activity include increasing children's understanding of religious teachings, increasing positive attitudes in daily life, and increasing parental involvement in guiding children's spiritual development. Overall, mentoring with religious insight succeeded in having a positive impact on the spiritual development of children in Kepuhrubuh Village